The penalty for the phenomenon of the students’ cheating in the exams - AL. Shawani, Nozad Ahmed Yassin (Opción, 2019)
The aim of the study is to investigate the penalty for the phenomenon of the student’s cheating in the exams via comparative qualitative research methods. As a result, the criminal confrontation with the taking educational and organizational measures before mentioned above is the best way to reduce the spread of the phenomenon of cheating in the exams. In conclusion, the student’s cheat in the exam is harmful to the community, because the student after graduating may practice a profession and fail in it.